2021
DOI: 10.3390/ijms22083920
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ouabain Prevents Na,K-ATPase Dysfunction and Targets AMPK and IL-6 in Disused Rat Soleus Muscle

Abstract: Sustained sarcolemma depolarization due to loss of the Na,K-ATPase function is characteristic for skeletal muscle motor dysfunction. Ouabain, a specific ligand of the Na,K-ATPase, has a circulating endogenous analogue. We hypothesized that the Na,K-ATPase targeted by the elevated level of circulating ouabain modulates skeletal muscle electrogenesis and prevents its disuse-induced disturbances. Isolated soleus muscles from rats intraperitoneally injected with ouabain alone or subsequently exposed to muscle disu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…A number of studies have reported that Na,K-ATPase undergoes internalization/endocytosis upon ouabain binding [ 70 , 71 ]. Chronic administration of ouabain (1 µg/kg/day for four days), which doubled circulating ouabain level [ 44 , 72 ], reduced the α2 Na,K-ATPase membrane content in the rat diaphragm and soleus muscles [ 73 ]. This was observed without changes in the total level of α2 Na,K-ATPase protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have reported that Na,K-ATPase undergoes internalization/endocytosis upon ouabain binding [ 70 , 71 ]. Chronic administration of ouabain (1 µg/kg/day for four days), which doubled circulating ouabain level [ 44 , 72 ], reduced the α2 Na,K-ATPase membrane content in the rat diaphragm and soleus muscles [ 73 ]. This was observed without changes in the total level of α2 Na,K-ATPase protein.…”
Section: Discussionmentioning
confidence: 99%
“…This was observed without changes in the total level of α2 Na,K-ATPase protein. This suggests that the elevated level of circulating ouabain modulates the α2 Na,K-ATPase subunit trafficking between its intracellular pool and the sarcolemma and/or its turnover in the membrane resulting in the reduced α2 Na,K-ATPase membrane abundance [ 73 ]. Thus, the HH-induced decrease in the level of circulating ouabain, as observed in this study, can cause an opposite effect—an increase in the α2 Na,K-ATPase membrane abundance, which we observed.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015 it was demonstrated that 24-72 h of rat hindlimb suspension specifically decreases the electrogenic activity of the Na,K-ATPase α2 isozyme and the resting membrane potential of soleus muscle fibers [34]. In 2021 the same research group detected the decrease in resting membrane potential of soleus muscle fibers as early as after 6 h of rat hindlimb suspension, and preventing Na,K-ATPase dysfunction rescues the resting membrane potential of soleus muscle fibers [35]. Earlier it was shown that the unloading-induced decrease in the resting membrane potential of soleus muscle fibers is accompanied by the sarcoplasmic accumulation of calcium ions after 3 days of unloading [32].…”
Section: Calcium Homeostasis Alterations In Skeletal Muscles During U...mentioning
confidence: 99%
“…Low-dose ouabain prevents both Na,K-ATPase and AMPK inactivation in soleus muscle during 6 h of rat hindlimb suspension. So, there is a possible functional link between AMPK and Na,K-ATPase inactivation [35]. The hindlimb suspension-induced AMPK inactivation is in turn triggered by an increase in the ATP/ADP ratio, which occurs as the result of soleus muscle contractile activity cessation at the early stage of the hindlimb suspension model of muscle unloading [1,40,41].…”
Section: Calcium Homeostasis Alterations In Skeletal Muscles During U...mentioning
confidence: 99%
“…This compound activates the Na, K ATPase and hyperpolarizes the sarcolemma [ 128 ]. Thus, ouabain can prevent sarcolemma depolarization and the disuse-induced dysfunction in rodent soleus muscle [ 129 ].…”
Section: Muscle Atrophy Observed In Different Physiopathological Cond...mentioning
confidence: 99%